The role of productivity in collective bargaining: Input or output or both? - Thomas Haipeter; Jor̈n Boewe; Johannes Schulten (Universität Duisburg-Essen, Institut Arbeit und Qualifikation (IAQ), 2018)
At a glance: Productivity can play a role in collective bargaining both as https://duepublico2.uni-due.de/receive/duepublico_mods_00040961an input and as an output; as an input it is a benchmark for wage agreements, as an output it is affected by the collective agreements. Our study of four sectors shows some fundamental differences concerning the role of productivity in collective bargaining agreements in different areas of the economy. Whereas productivity is still important to define and legitimize wage demands in the metalworking sector, it is no relevant benchmark in the service sectors we analysed. The recognition of productivity as an input factor seems to be important for regarding it as an output factor as well. It is only in the metalworking sector where productivity as an output has some significance. There are three collective bargaining issues focusing on productivity: performance based pay, profit sharing and, most explicitly, derogations from collective bargaining agreements.
urn:nbn:de:hbz:464-20180321-151234-2
Keywords: 300